Graph-Based AI/ML Algorithms for Real-Time Security Event Correlation and Attack Campaign Detection - Vincent Kanka; Akhil Reddy Bairi; Abdul Samad Mohammed (Journal of Science & Technology, 2022)
The exponential growth of cybersecurity threats and the increasing sophistication of attack campaigns necessitate the development of advanced methodologies for detecting and mitigating malicious activities in real-time. Traditional intrusion detection systems and security information and event management (SIEM) tools often fall short in effectively correlating distributed security events, particularly in the context of coordinated and multi-vector attack chains. This paper explores the application of graph-based artificial intelligence (AI) and machine learning (ML) algorithms, combined with knowledge graphs, as a transformative approach for real-time security event correlation and attack campaign detection.Graph-based learning models, inherently capable of representing and analyzing relationships in complex datasets, offer significant advantages in identifying hidden patterns, dependencies, and anomalies across distributed security events. Knowledge graphs, on the other hand, provide a robust framework for integrating disparate sources of information, enabling the establishment of contextual relationships between entities such as IP addresses, user accounts, and system events. This synergistic application of graph-based AI/ML and knowledge graphs facilitates the construction of a comprehensive security ontology, thereby enhancing the accuracy and efficiency of event correlation and attack detection.The study emphasizes the deployment of graph neural networks (GNNs), community detection algorithms, and graph-based clustering techniques as core components of advanced security analytics. Practical implementations leveraging tools like Splunk AI and Elastic Security are discussed, highlighting their capabilities in ingesting, processing, and visualizing graph-structured data for actionable insights. Specifically, Splunk AI's ability to integrate machine learning pipelines with graph analytics and Elastic Security's scalability in handling large volumes of graph data are demonstrated as pivotal in addressing real-world cybersecurity challenges.A comparative evaluation of these tools is presented, supported by experimental results on benchmark datasets and synthetic attack scenarios. The findings illustrate the efficacy of graph-based methods in detecting coordinated attack campaigns, such as advanced persistent threats (APTs), lateral movement, and data exfiltration, with reduced false positives and improved response times compared to conventional methods. Moreover, the integration of real-time event correlation with predictive modeling capabilities enables proactive threat hunting and incident response, significantly enhancing the overall security posture of organizations.The paper also delves into the technical challenges associated with implementing graph-based security analytics, including computational complexity, scalability, and the need for high-quality, labeled datasets. Strategies for overcoming these challenges, such as leveraging distributed graph processing frameworks and employing semi-supervised learning techniques, are discussed in detail. Furthermore, the ethical implications and privacy concerns arising from the use of sensitive data in graph-based security models are critically examined, along with recommendations for ensuring compliance with data protection regulations.
Keywords: graph-based learning; knowledge graphs; real-time detection